Cyberbullying among University Students: Gendered Experiences, Impacts, and Perspectives. (3rd November 2014) - Faucher, Chantal; Jackson, Margaret; Cassidy, Wanda
Abstract : Cyberbullying is an emerging issue in the context of higher education as information and communication technologies (ICT) increasingly become part of daily life in university. This paper presents findings from 1925 student surveys from four Canadian universities. The overall findings are broken down to determine gender similarities and differences that exist between male and female respondents' backgrounds, ICT usage, experiences with cyberbullying, opinions about the issue, and solutions to the problem. We also examine the continuities between these findings and those of earlier studies on cyberbullying among younger students. Our findings also suggest that gender differences, which do emerge, provide some support for each of the three theoretical frameworks considered for understanding this issue, that is, relational aggression, cognitive-affective deficits, and power and control. However, none of these three models offers a full explanation on its own. The study thus provides information about cyberbullying behaviour at the university level, which has the potential to inform the development of more appropriate policies and intervention programs/solutions to address the gendered nature of this behaviour.